Faktor Yang Ada Hubungan Dengan Penderita Acute Coronary Syndrome Di Beberapa Lokasi Di Wilayah Asia Periode Tahun 2011 Sampai Dengan Tahun 2019 - Mardewiyanti, Mardewiyanti; Sartika, Suriana Dwi; Amirudin, Tedy (Bosowa Medical Journal, 2024)
Acute coronary syndrome is a picture of ischemic conditions in the myocardium (heart muscle) caused by plaque in the coronary arteries and gets worse with the thrombosis process, causing obstruction which causes reduced perfusion to the myocardium. The purpose of this study was to determine the factors associated with patients with acute coronary syndrome based on hypertension, diabetes, smoking, dyslipidemia and obesity. The research method used in this study is analytic by using a literature objective approach on factors that are associated with patients with acute coronary syndrome in the journal of medical research results in the literature. The results of research from eleventeen literature journals show that there is a relationship between acute coronary syndrome in several locations in the Asian region from 2011 to 2019 it can be concluded that in patients with acute coronary syndrome, namely hypertension (p-value = <0.001), diabetes (p-value = <0.001), smoking (p-value = <0.001), dyslipidemia (p-value = <0.001), obesity (p-value = <0.001), had a significant relationship with acute coronary syndrome in several locations in Asia during the period It is hoped that this research will be able to increase the participation of the health department, in collaboration with health workers and community leaders in preventing and dealing with acute coronary syndrome events.